2024
DOI: 10.1007/s10554-024-03054-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the cardiac output at rest and during exercise stress using real-time cardiovascular magnetic resonance imaging in HFpEF-patients

Alexander Schulz,
Hannah Mittelmeier,
Lukas Wagenhofer
et al.

Abstract: This methodological study aimed to validate the cardiac output (CO) measured by exercise-stress real-time phase-contrast cardiovascular magnetic resonance imaging (CMR) in patients with heart failure and preserved ejection fraction (HFpEF). 68 patients with dyspnea on exertion (NYHA ≥ II) and echocardiographic signs of diastolic dysfunction underwent rest and exercise stress right heart catheterization (RHC) and CMR within 24 h. Patients were diagnosed as overt HFpEF (pulmonary capillary wedge pressure (PCWP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Non-invasively quantified atrial function in diastolic dysfunction and HFpEF was confirmed as an important parameter in general for the diagnosis and prognostication in HFpEF as it is a key element in the disease's pathophysiology. 15,30,31 On the one hand, atrial EAT could aggravate commonly known haemodynamic challenges by further restriction and might limit the compensatory function of the atrium in ventricular diastole. 32 On the other hand, those impairments by atrial EAT align with the assumption of the development of an atrial cardiomyopathy, which nurtures LA malfunction as a central role in diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasively quantified atrial function in diastolic dysfunction and HFpEF was confirmed as an important parameter in general for the diagnosis and prognostication in HFpEF as it is a key element in the disease's pathophysiology. 15,30,31 On the one hand, atrial EAT could aggravate commonly known haemodynamic challenges by further restriction and might limit the compensatory function of the atrium in ventricular diastole. 32 On the other hand, those impairments by atrial EAT align with the assumption of the development of an atrial cardiomyopathy, which nurtures LA malfunction as a central role in diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%